Crab and Cockle Shells as Catalysts for the Preparation of Methyl Esters from Low Free Fatty Acid Chicken Fat - Boey, Peng-Lim; Maniam, Gaanty Pragas; Abd Hamid, Shafida; Ali, Dafaalla Mohamed Hag (American Oil Chemists' Society Press, 2010)
The use of waste oils/fats, as well as catalysts from waste materials, for producing biodiesel via transesterification have been of recent interest. As such, in the present work, the transesterification of chicken fat using crab and cockle shells as a catalyst was attempted. X-ray diffraction (XRD) and electron dispersive X-ray (EDX) results show that, upon thermal activation, both shells transformed into CaO, the active ingredient that catalyzes the reaction. In addition, the catalytic performance of individual shells as well as the combination of both shells in various ratios was similar. Under the optimal reaction conditions of 4.9 wt% catalyst amount and 0.55:1 methanol to oil mass ratio, methyl esters conversion above 98% was achieved in 3 h. The chicken fat methyl esters that were produced were found to meet several key specifications of biodiesel based on EN 14214 and ASTM D6751 test procedures.